2006
DOI: 10.2337/diabetes.55.04.06.db05-1329
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Diabetic Nephropathy in Mice Lacking the Peroxisome Proliferator–Activated Receptor α

Abstract: Peroxisome proliferator-activated receptor (PPAR)␣, a member of the ligand-activated nuclear receptor superfamily, plays an important role in lipid metabolism and glucose homeostasis and is highly expressed in the kidney. The present studies were aimed at determining the role of PPAR␣ in the pathogenesis of diabetic nephropathy using PPAR␣-knockout mice and cultured murine mesangial cells. Diabetes was induced using a low-dose streptozotocin protocol in 8-week-old male 129 SvJ PPAR␣-knockout and wild-type mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 39 publications
7
95
0
1
Order By: Relevance
“…Previously, we found that PPARa activity in kidneys was inversely correlated with lipid accumulation and oxidative stress in type 1 and 2 diabetic animals. 21,22 In this study, we found that oxidative stress, as reflected by glomerular and 24-h urinary 8-OH-dG and 8-epi-PGF 2a levels, was closely related to intrarenal TG and FFA contents. Interestingly, fenofibrate treatment significantly improved reduced systemic and intrarenal bioavailability of NO and completely reversed the oxidative stress and inflammation in kidneys induced by the HF diet.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Previously, we found that PPARa activity in kidneys was inversely correlated with lipid accumulation and oxidative stress in type 1 and 2 diabetic animals. 21,22 In this study, we found that oxidative stress, as reflected by glomerular and 24-h urinary 8-OH-dG and 8-epi-PGF 2a levels, was closely related to intrarenal TG and FFA contents. Interestingly, fenofibrate treatment significantly improved reduced systemic and intrarenal bioavailability of NO and completely reversed the oxidative stress and inflammation in kidneys induced by the HF diet.…”
Section: Discussionmentioning
confidence: 80%
“…16 PPARa is also well known as a determinant of the development of hypertension and renal damage, especially in AT-II-induced hypertensive rats. 21,23,24,30 Induction of the renal expression of CYP4A enzymes in the kidney using fibrate compounds has been reported to lower BP in SHR, stroke-prone SHR and Dahl salt-sensitive rats. 31,32 We found the inverse pattern of PPARa expression in kidneys of WKY-HF rats compared with that in SHR-HF animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, standardised benchmarks of hyperglycaemia, albuminuria and measurements of renal failure remain to be developed for different inbred strains of mice. The most glaring deficiency has been the lack of a mouse model of diabetes that develops progressively worsening renal insufficiency [63], although recent reports have given positive indications that this experimental problem will be overcome [64,65]. Despite the preceding caveats regarding the difficulties in phenotyping renal function in mice, the use of transgenic mouse models has provided a better understanding of mechanisms that exacerbate diabetic nephropathy [63,66].…”
Section: Retinopathy the Overall Results For Two Studies Of Diabetic Rmentioning
confidence: 99%